COMPARATIVE STUDY OF THE INDICES THAT DETERMINE THE MOTOR TRAINING AS A FACTOR OF THE CHOREOGRAPHIC TRAINING OF THE STUDENTS OF THE PROFILE FACULTIES - Salup Mărioara (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
Choreographic training is one of the basic links, which aims to acquire a complex of movements in accordance with the music. The choreographic training of the students has a beneficial role in the motor training of the profile students. The paper aims to develop the motor training of profile students with the help of the experimental program. Methods for assessing the level of motor readiness are speed, strength and general coordination tests. One of the objectives would be the need for choreographic training from the point of view of the professors from the profile faculties and the level of acquisition of the elements necessary for the choreographic training.